Diabetes and biodistribution of pertechnetate (Na99mTcO4) in rats - Azevedo, Ítalo Medeiros; Fernandes, Daniele Pimentel; Costa, Ticiana Cabral; Araújo-Filho, Irami; Rego, Amalia Cintia Meneses; Carvalho, Marília Daniela Ferreira; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2010)
PPurpose:This study aimed to clarify if diabetes induced in rats changes the biodistribution of the radiopharmaceutical sodium pertechnetate (Na99mTcO4) and, consequently, the accuracy of the scintigraphic exams. Methods: We used 14 male Wistar rats, randomly allocated in 2 group: the diabetic group (D) rats (n=7) were submitted to the induction of diabetes with streptozotocin, and 7 non diabetic rats were used as controls (C). After 7 days, in the 14 animals it was administered 0,1 mL of Na99mTcO4 (0.66 MBq) through orbital plexus and, after 30 minutes, the radiopharmaceutical sodium pertechnetate was evaluated, being compared the uptske of this in the several studied organs of diabetic animals and controls.Results: The biodistribution of Na99mTcO4 was significantly higher in the liver and smaller in the bladder, thyroid and stomach of diabetic mice when compared to the control group rats. Conclusion: Diabetes induced in rats alters the biodistribution of Na99mTcO4, and this finding could have clinical implications on scintigraphic exams.